Analisis Faktor Risiko Ergonomi terhadap Keluhan Musculoskeletal Disorders (MSDs) Pekerja Kurnia Lurik Sewon Bantul Daerah Istimewa Yogyakarta (DIY) - Novita Lizza Anggraini; Nur Arfian; Santosa Budiharjo (G-Tech: Jurnal Teknologi Terapan, 2024)
Occupational safety and health (K3) in medium-sized business enterprises (UKM) is really needed because almost 70% of SMEs in Indonesia do not know about occupational safety and health (K3). Occupational diseases (PAK) in weaving workers are Musculoskeletal Disorders (MSDs). The aim of the research is to analyses the ergonomic factors that result in MSDs complaints among workers. Using quantitative methods with analytical observational research using a cross-sectional design. The number of respondents was 30 respondents. The Rapid Entire Body Assessment (REBA) method is used to assess work posture, the Nordic Body Map (NBM) method is used to assess work fatigue (subjective), Lactate Analysis is used to measure work fatigue (objective). The results of the research show that work posture, work fatigue (subjective), work fatigue (objective) have a high risk of MSDs complaints while work period and work duration result in risks to organization.